Effects of the economic crisis on rural household incomes in Romania - Anca Dachin; Sercin Ali (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
The rural area in Romania has experienced a transformation process in the last decade mainly due to overall economic growth and to the effects of EU integration. The agricultural activity is still dominant, even if the share of employment in this sector followed a strong decreasing trend. The economic crisis starting in 2008 produced structural changes in the use of labor force, with impact on the population's income. The paper presents an empirical analysis of the economy's evolution from macroeconomic perspective and focuses on the effects of the crisis on the rural area. The research uses the multiple linear regression to analyze the impact of economic growth and employment on investment in agriculture and on total income of rural households. The results show that investment in agriculture is connected to the variation of GDP and has a negative correlation with employment in agriculture. The household income has a high sensitivity to GDP changes, which have effects on salaries and social provisions in rural areas. However the subsistence component of the rural activities determines an important inertia of the total household income, which is very little influenced by investments in agriculture and is less reactive to the economic crisis compared to urban areas.
Keywords: 330; economic crisis; investment; employment in agriculture; income of rural households